2014
DOI: 10.3892/ijmm.2014.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of HDAC1 by miR-449a upregulates Runx2 and promotes osteoblast differentiation

Abstract: Human-induced pluripotent (iPS) cells can be induced to differentiate into osteoblasts, but the process is inefficient and time-consuming. Previous studies indicated a close association between the expression of Runx2 and osteoblast differentiation, and established that the transcriptional activation of the Runx2 gene was closely associated with histone acetylation. microRNA-449a (miR-449a) represses HDAC1 expression, thereby regulating histone acetylation. In the present study, whether the expression of miR-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Expression of class I HDACs (HDAC1, -2 and -3) has been reported to negatively correlate with the expression the key osteogenic transcription factor Runx2 [20][21][22]. In our group, we could show that the upregulation of HDAC6 results in shortened and deformed primary cilia, which impairs the mechanically driven osteogenesis [27].…”
Section: Rhtgf-β1 Treatment Significantly Downregulated Hdac9 Expressmentioning
confidence: 47%
See 2 more Smart Citations
“…Expression of class I HDACs (HDAC1, -2 and -3) has been reported to negatively correlate with the expression the key osteogenic transcription factor Runx2 [20][21][22]. In our group, we could show that the upregulation of HDAC6 results in shortened and deformed primary cilia, which impairs the mechanically driven osteogenesis [27].…”
Section: Rhtgf-β1 Treatment Significantly Downregulated Hdac9 Expressmentioning
confidence: 47%
“…Improved osteogenic differentiation by using small chemical inhibitors for HDACs [16,18] points towards a direct acetylation-dependent mechanism. This is described for HDAC1 and -3 overexpression, which inhibits the expression of the key osteogenic transcription factor Runx2 [20][21][22]. Furthermore, the overexpression of HDAC6 causes a de-acetylation of α-tubulin, resulting in damaged primary cilia and impaired mechanically driven osteogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-449a has been found to induce differentiation of other cell types. Liu et al ectopically expressed miR-449a in vitro in pluripotent cells, and detected osteoblast differentiation markers after several days [52] . The differentiation of these cells was correlated with the down-regulation of HDAC1, a direct target of miR-449a [52] .…”
Section: Mirna-449amentioning
confidence: 99%
“…Liu et al ectopically expressed miR-449a in vitro in pluripotent cells, and detected osteoblast differentiation markers after several days [52] . The differentiation of these cells was correlated with the down-regulation of HDAC1, a direct target of miR-449a [52] . A study done by Capuano et al suggested that miR-449a may also be involved in the differentiation of intestinal cells [53] .…”
Section: Mirna-449amentioning
confidence: 99%